Changes in diet quality and risk of hypertension in adults: Evidence from the NCDs cohort study, Bogor, Indonesia - Salsabil Naqiyyah; Ikeu Tanziha; Dodik Briawan; Woro Riyadina (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
The prevalence of hypertension is increasing globally, including in Indonesia. Therefore, dietary patterns such as the Dietary Approaches to Stop Hypertension (DASH) diet are recommended to help control blood pressure. However, research on adherence to the DASH diet and its relationship with blood pressure in Indonesia is still limited, especially in long-term cohort studies. This study aimed to analyze the relationship between changes in dietary quality and blood pressure. This study design is a retrospective cohort study used secondary data from the Non-Communicable Disease Risk Factor Cohort Study (FRPTM) conducted in five urban villages in Bogor City from 2011 to 2018, involving 1,724 adult respondents. The analysis was performed using the chi-square test and multiple logistic regression analyses. The results showed no significant relationship between diet quality at baseline, follow-up, or changes in diet quality and the blood pressure. However, individuals with worsening diet quality had a 1.2-fold higher risk of developing hypertension (OR=1.237; 95%CI=0.886–1.727), while those with stable poor diet quality had a 1.3-fold higher risk (OR=1.285; 95%CI=0.905–1.824) than individuals with improved diet quality. In conclusion, these findings suggest that a decline in dietary quality may increase the risk of hypertension.